غزو العراق لدولة الكويت (1990م): دراسة تحليلية لخلفياته وأسبابه وتداعياته - مصعبي، سلامه علي حسين الزهما (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research focuses on the study of the nature of Iraqi-Kuwaiti relations since the independence of Kuwait in 1961 and up to its annexation by Iraq in 1990. It explores the underlying factors for this annexation and pursues its development, as well as the regional and international reactions to this crisis. The study suggests that the annexation was indeed a crime committed against both Kuwait and Iraq in particular and the Arab region in general. It led to a split in the Arab front and the loosening of the Arab brotherly relations, which, in turn, caused internal conflicts and the emergence of a terrorist Islamic leadership. Consequently, the Arab region has become a theatre for revolts- the so called “Arab spring”, 'creative chaos” or “the new Middle East” as coined by the American government. Arab institutions, like the Arab League, has been marginalised, treaties between Arab states, particularly the treaty of mutual defence, have no longer been respected and the Arab financial resources have been depleted. The annexation and its aftermath cost around a trillion dollars, a sizable amount of money that has been much needed to contribute in the economic development and to introduce developmental reforms in the Arab world. The impact of the annexation goes beyond the economic dimension to the social arena of both the Kuwaiti and Iraqi peoples. The annexation has also led to the tilting of the balance of power in the Middle East in favour of non-Arab forces, like Israel, Iran and Turkey. It also led to a transformation in the American strategies and rearrangements of plans and their execution in favour of America's interest and security and that of Israel in the Gulf and the Middle East in general. The study adopted several methods. It employed the historical method to explore the historical background of the Iraqi- Kuwaiti conflict, and to pursue the path of the political, economic and military relations between the two countries that ultimately led to the Iraqi annexation of Kuwait in 1990. The analytical method has been used to analyse the contents of books, documents and other references in English and Arabic on the Iraqi-Kuwaiti relations and the Iraqi annexation of Kuwait – its background, underlying factors and repercussions. The inductive method was also used to understand and evaluate data given in personal interviews conducted with individuals, academicians and politicians familiar with the dynamics of the region.